DAMPAK KEBIJAKAN QUANTITATIVE EASING DAN TAPERING OFF TERHADAP PERPAJAKAN INDONESIA: TINJAUAN LITERATUR - Aribowo, Irwan Aribowo; Sigit, Tri Angga; Mahrus, Moh. Luthfi (Politeknik Keuangan Negara STAN, 2023)
Analysis of the impact of Quantitative Easing (QE) by the US Federal Reserve and the Tapering Off policy on developing countries including Indonesia, it is known that QE affects capital flows, currency exchange rates and financial markets in developing countries. The impact involves changes in fiscal policy, incentives, and changes in tax rates to address changes in capital flows and the effects of QE. Additionally, changes in the money supply affect local currency depreciation, production costs, and inflation. In the Indonesian context, investment capital withdrawals and Bank Indonesia policies play an important role in dealing with the impact of QE. Therefore, policy recommendations involve balancing monetary and fiscal policies, and considering fiscal variables in economic policy making. Policy measures including fiscal incentives, changes in tax rates, and consideration of fiscal variables in policy making reflect the important role of tax in managing the economic impact of QE and Tapering Off policies, especially in the context of developing countries such as Indonesia. Fiscal policy, including changes in tax rates, is used as an instrument to address changes in capital flows, exchange rates, and financial flows. It shows how taxes can be used as a policy tool to offset changes in the volatile global economic situation.